Ecthyma Contagiosum (Orf Virus) Masquerading as Subcorneal Pustular Dermatosis: A Diagnostic Pitfall in an Adolescent - Lisa Alverina; Luh Made Mas Rusyati; Suharmono Hadi; Herman Saputra (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Ecthyma contagiosum (Orf) is a zoonotic viral infection caused by a Parapoxvirus, typically presenting as a self-limiting, solitary cutaneous lesion on the hands of occupationally exposed individuals. Atypical, multifocal, or pustular presentations can pose a significant diagnostic challenge, mimicking various inflammatory dermatoses. Case presentation: We present the case of a 17-year-old female with no direct animal contact who developed a progressive, widespread, and painful pustular eruption on her extremities over three weeks. The clinical presentation was highly suggestive of Subcorneal Pustular Dermatosis (SPD), prompting treatment with systemic corticosteroids, which led to clinical worsening. A delayed epidemiological history revealed an environmental link to a nearby goat farm and a family cluster of similar, milder lesions. A diagnostic punch biopsy was pivotal, revealing viral cytopathic effects, including extensive ballooning degeneration and epidermal necrosis, inconsistent with SPD. Subsequent bacterial culture confirmed superinfection with Enterobacter cloacae ssp. cloacae. The diagnosis was established by the pathognomonic histopathological findings. Conclusion: The patient’s steroid therapy was immediately ceased, and targeted antibiotic therapy was initiated, leading to complete resolution. This case highlights the Orf virus as a critical clinical chameleon and a diagnostic pitfall for generalized pustular eruptions. It underscores the necessity of a high index of suspicion for zoonoses, even in non-occupational settings, and confirms the indispensable role of histopathology in differentiating viral cytopathy from sterile neutrophilic dermatoses to prevent iatrogenic harm from inappropriate immunosuppression.